Genosida dan Trauma dalam Novel Laut Bercerita - Rizky Amelya Furqan; Armini Arbain; Selfi Mahat Putri (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
After Indonesia's independence, various internal conflicts occurred which caused several major upheavals. These include Permesta, PRRI, 1965, and 1998 incidents. Not only upheavals, but also crimes, such as rape, looting, torture, and even genocide. This is what makes literary works present by recounting incidents of violence or disappearances that occurred during the upheaval, one of which is the novel Laut Bercerita by Leila S. Chudori which discusses the events of 1998. Genocide events can be one of the factors that cause trauma, so Hirsch explained that genocide can be a factor in the occurrence of memory transmission to the next generation. Thus, an analysis of how genocide is described to form trauma to the victim or the people around the victim is interesting to explore. The research method used in this study is descriptive narrative analysis obtained through novels or other supporting references that support the presence of a genocide narrative so that trauma can be analyzed by victims or the people around them. The result of this study is that there was a genocide in the Wiratna and Wirasena communities, they were considered to have carried out activities against the government resulting in detention, torture, and disappearances. This incident of disappearance or genocide caused the victim who managed to escape, his family, and even those around the victim to be traumatized by this event. Although, in the end, they were able to start accepting reality.